Penerapan Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Matematika Peserta Didik kelas VIII-A SMPN 1 Mataram - Dewi, Oktavia; Baidowi, Baidowi; Suntoko, M. Iwan (Griya Journal of Mathematics Education and Application, 2025)
This study was motivated by the previous learning process, which tended to be delivered uniformly without considering the varying ability levels of students. This approach resulted in low overall learning achievement at the class level. The objective of this study is to improve the mathematics learning outcomes of Grade VIII A students at SMPN 1 Mataram through the implementation of the Teaching at the Right Level (TaRL) approach, which is a learning strategy based on students’ ability levels. This research employs a Classroom Action Research (CAR) design, consisting of two cycles. Each cycle includes the stages of planning, implementation, observation, evaluation, and reflection. Data were collected through observation and learning outcome tests. The results of the study are as follows: (1) In the first cycle, the students' classical mastery reached 72.5%, with an average score of 73. These results did not meet the minimum success criterion for classical mastery, which is set at 85%. (2) In the second cycle, there was a significant improvement in learning outcomes, with classical mastery reaching 87.5% and an average score of 90. This indicates that the implementation of the Teaching at the Right Level (TaRL) approach can improve students' learning outcomes